The algorithm of PARALLEL COMPUTING OF THE NONISOTHERMAL HEAT AND MOISTURE MIGRATION TASK IN NATURAL DISPERSE ENVIRONMENT - P. K. Shalkevich; S. P. Kundas; I. A. Gishkeluk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The modeling of nonisothermal heat and moisture transfer in natural disperse environment is considered. It is necessary to apply parallel computing techniques for solving these problems in three-dimensional setting. An algorithm of parallel computing of nonisothermal heat and moisture transfer is based on the creation of distributed data array by solving a system of equations of nonisothermal heat and moisture transfer with the use of finite element method.